Descriptor Neural Networks with Arbitrary Characteristic Inde - Hahanov, V.; Rutkas, A. (ХНУРЭ, 2009)
We consider a difference descriptor system and its modeling with the help of a neural network. The corresponding descriptor network is a special connection of dynamic and static neurons. The network configuration is defined by the Weierstrass’s normal form of regular matrix sheaf.
Keywords: Weierstrass’s normal form; neural network; descriptor system